Photoclick Reaction Constructs Glutathione-Responsive Theranostic System for Anti-Tuberculosis - Zheng, Judun; Long, Xun; Chen, Hao; Ji, Zhisheng; Shu, Bowen; Yue, Rui; Liao, Yechun; Ma, Shengchao; Qiao, Kun; Liu, Ying; Liao, Yuhui (Frontiers in Molecular Biosciences, 2022)
Tuberculosis (TB) is a virulent form of infectious disease that causes a global burden due to its high infectivity and fatality rate, especially the irrepressible threats of the latent infection. Constructing an efficient strategy for the prevention and control of TB is of great significance. Fortunately, we found that granulomas are endowed with higher reducibility levels possibly caused by internal inflammation and a relatively enclosed microenvironment. Therefore, we developed the first targeted glutathione (GSH)-responsive theranostic system (RIF@Cy5.5-HA-NG) for tuberculosis with a rifampicin (RIF)-loaded near-infrared emission carrier, which was constructed by photoclick reaction-actuated hydrophobic-hydrophobic interaction, enabling the early diagnosis of tuberculosis through granulomas-tracking. Furthermore, the loaded rifampicin was released through the dissociation of disulfide bond by the localized GSH in granulomas, realizing the targeted tuberculosis therapy and providing an especially accurate treatment mapping for tuberculosis. Thus, this targeted theranostic strategy for tuberculosis exhibits the potential to realize both granulomas-tracking and anti-infection of tuberculosis.